Wireless internet 6th International ICST Conference, WICON 2011, Xi'an, China, october 19-21, 2011, revised selected papers - International ICST Conference, WICON 2011 (Lecture notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th International ICST Conference on Wireless Internet (WICON 2011) held in Xi’an, Shaanxi, China in October 2011. The 55 revised full papers were carefully selected from numerous submissions and focus on research in telecommunication and networking and development in information and communication technologies. The papers are presented in 10 technical sessions and cover topics as video streaming over OFDMA downlink systems, cognitive radio networks, distributed antenna systems, joint source channel coding, multiuser MIMO systems, signal detection, frequency synchronization in 3GPP LTE systems, visual cognitive radio, wireless relay networks, and network flow identifying methods.